Getting Repentance Right: Luther's Reformation Refocused - Appold, Kenneth G. (Theology today, 2018)
Luther's Reformation began with a debate over proper repentance, a fact that tends to get overlooked in most accounts of its history. By focusing on a close reading of the first five of Luther's "95 Theses," the following article examines that debate in its context, seeks to understand Luther's theological insights and places them in conversation with contemporary thoughts and practices of repentance.